PRACTICES OF TOBACCO CONSUMPTION AND OTHER DRUGS AMONG STUDENTS OF HEALTH´S SCIENCES OF A PRIVATE UNIVERSITY. LIMA –PERÚ - Zárate, Margot; Zavaleta, Alfonso; Danjoy, Delia; Chanamé, Eva; Prochazka, Ricardo; Salas, María; Maldonado, Viviana (Investigación y Educación en Enfermería, 2008)
<!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Objectives: to identify tobacco and other drugs use among Health Sciences undergraduates. Methodology and Materials: a descriptive self administered cross sectional survey about 2.074 private students in 9 health careers in Lima. Results and Discussion: the life prevalence (PV) and current tobacco use were 82.0% and 38.7%. Smoking or the desire of smoking was the ﬁrst thing in the morning for 15.6% of the students. Since 16 years of age 43.8% of them smoke tobacco. Twenty ﬁve per cent of them smoked for the ﬁrst time at a party and 45.8% still smoke at social events. Exposition to environmental smoke outside home was experienced by 68.5%. There was signiﬁcant association between the smoking habits of parents, brothers and friends and the fact of being smoker or non smoker. Alcohol PV: 94.3%. Marihuana: 16.7%. Cocaine basic paste: 7.5% Cocaine HCL: 7.6%. Conclusions: tobacco and drugs use was widespread among the students. Initiation to smoking occurs during adolescence. There is high environmental exposition to tobacco outside home and parental tobacco use is linked to smoking.